Water erosion risks and their environmental impacts on Darbandikhan city according to the (EPM) model. - Saber, Prof.Dr. Saya Salam Saber; Hamid, Mohammed Jumaa Hamid (Sulaimani Journal for Humanities, 2025)
The research aims to identify the characteristics of the water erosion process in the city of (Darbandikhan) and the extent of the geomorphological risks caused by the process through the use of the EPM model, where the research issue is centred on the amount and volume of soil lost, to show us the most important damage, which is the loss of soil nutrients and the change in its texture, which leads to the erosion of the surface layer, and thus poses a danger to the layers below it, which are often of a softer texture than those above it. The results of the entire process of water erosion are the destruction of the ground structure, the loss of the productivity of the soil and its ineffectiveness or the possibility of benefiting from it in various human activities, and among its obvious damages in the city of Darbandikhan and the boundaries of the study area is the destruction of roads, building foundations, arches and other engineering constructions, especially in the case of the presence of slopes. This is in addition to its environmental impacts such as the runoff of pollutants such as oils and heavy metals from the streets, sediment deposition and the resulting clogging of waterways, infrastructure erosion and environmental imbalance, where there is an interactive relationship between the pollution of water bodies and the deterioration of irrigation on the one hand and the impact of the local food chain in the region on the other. On the other hand, relying on the (Gavrilovic) model, based on the rockiness of the study area, the average degree of slope, land cover, rainfall and temperature index taken from several climate stations, and then relying on satellite data, the levels of water erosion in the study area were classified into six categories, where the generalized or comprehensive category reached about (48%) and the category of strong erosion by (24, 9%) of the area of the study area of 24. 9 km2.
Keywords: Soil erosion; EPM model; Darbandikhan city; environmental impact